A Real-business-cycle Model with a Stochastic Capital Share: Lessons for Bulgaria (1999–2018). (February 2020) - Vasilev, Aleksandar
We allow for a stochastic capital share into a real-business-cycle setup with a government sector. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999–2018). We investigate the quantitative importance of the variability in capital share for cyclical fluctuations in Bulgaria. In particular, allowing for a stochastic capital share in the model increases variability of investment and employment, at the cost of decreasing the volatility of wages, and causing employment to become countercyclical. JEL Classification: E24, E32